The magician of Tiger Castle - Sachar, Louis, 1954- (Ace, 2025)
"The beloved author of Holes presents his first adult novel, a modern fantasy classic of forbidden love, a crumbling kingdom, and the unexpected magic all around us. Long ago and faraway (and somewhere south of France), lies the kingdom of Esquaveta. There, Princess Tullia is in nearly as much peril as her struggling kingdom. Esquaveta desperately needs to forge an alliance with Oxatania, and to that end, Tullia's father has arranged a marriage between her and the odious Oxatanian Prince. However, one month before the "Wedding of the Century," Tullia falls in love with a lowly apprentice scribe. The king turns to Anatole, his much-maligned magician. Seventeen years earlier, when Anatole first came to the castle, he was regarded as something of a prodigy. But after a long series of failures--the latest being an attempt to transform sand into gold--he has become the object of contempt and ridicule. The only one who still believes in him is the princess. When the king orders Anatole to brew a potion that will ensure Tullia agrees to the wedding, Anatole is faced with an impossible choice. With one chance to save the marriage, the kingdom, and of most importance to him, his reputation, will he betray the princess--or risk ruin?"--